AN EVALUATION OF TOEFL MATRICULATION PROGRAM FOR STAIN STUDENTS - Leffi Noviyenty (UIN Alauddin Makassar, 2018)
This is an expose facto reserach which analysed and evaluated a program done in 2016 at Language Center in State College of islamic Studies (STAIN) Curup. The purposes of this study iwas to evaluate the improvement of students' score on TOEFL particularly those who followed TOEFL Matriculation Program at Language Center. The improvement were investigated from three aspects of TOEFL, listening comprehension, structure and written expression and reading comprehension. This research also searched the strategies used by lecturers in teaching TOEFL during the program, and the students' motivation in following the program. Document analysis in the form of students' score for pre and post program, checklist, interview guidance and questionnaire were the instruments of this study. The data was analyzed by mix method. There were 2 English lecturers and 30 students who represented all study program in STAIN Curup. The findings showed that there was a significant improvement of students' TOEFL score after they followed the TOEFL matriculation program at Language Center. The score of each aspect of TOEFL also increased significantly. The lecturers also used suitable strategies in teaching TOEFL based on the need of students. Furthermore, the students' motivation in following the TOEFL matriculation Program was also high. It is suggested that this program should be continued by involving more students and improving the quality of program in the future.